Project Management - Dennis Lock (New York Routledge, 2019)
Dennis Lock's masterly exposition of the principles and practice of project management has been pre-eminent in its field for 45 years and was among the first books to treat project management as a holistic subject. But Project Management has been kept completely up to date by regular and sensitive revisions to ensure that it remains fresh and totally relevant. Project Management explains the entire project management process in great detail, demonstrating techniques from simple charts to detailed computer applications. Everything is reinforced with clear diagrams and case examples, many new for this edition. The author has expanded discussion of topics such as supply chain management and the project management office (PMO), and there are new chapters about implementing change management projects and the role of senior managers in supporting projects. Obsolescent or less frequently used methods have been stripped out. Students have always commented on this book's reader-friendly style, which is free of unnecessary jargon, with clear diagrams and a construction that is logically organized, well indexed and simple to navigate. This Tenth Edition is certain to maintain the book's acclaimed status as the standard work for managers and students alike.
Keywords: Work breakdown structure; Project management; Textbooks; Planning and Control of Projects (BIN2051-N); Projects and Organisations (BIN1070-N)